2011
DOI: 10.1016/j.neuron.2011.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Intron Sequence-Retaining Transcripts Can Be Dendritically Targeted via ID Element Retrotransposons

Abstract: RNA precursors give rise to mRNA after splicing of intronic sequences traditionally thought to occur in the nucleus. Here, we show that intron sequences are retained in a number of dendritically-targeted mRNAs, using microarray and Illumina sequencing of isolated dendritic mRNA as well as in situ hybridization. Many of the retained introns contain ID elements, a class of SINE retrotransposon. A portion of these SINEs confers dendritic targeting to exogenous and endogenous transcripts showing the necessity of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 44 publications
4
146
0
2
Order By: Relevance
“…What might label specific mRNAs for dendritic targeting? Buckley et al have identified ID element retrotransposons, a retained class of short interspersed repetitive elements (SINEs), within the introns of several dendritically targeted mRNAs (Buckley et al, 2011). These sequences are sufficient for targeting both endogenous and exogenous transcripts to dendrites, and, accordingly, appear to influence protein distribution within the cell.…”
Section: Rna Targeting and Local Protein Translation In Dendritesmentioning
confidence: 99%
“…What might label specific mRNAs for dendritic targeting? Buckley et al have identified ID element retrotransposons, a retained class of short interspersed repetitive elements (SINEs), within the introns of several dendritically targeted mRNAs (Buckley et al, 2011). These sequences are sufficient for targeting both endogenous and exogenous transcripts to dendrites, and, accordingly, appear to influence protein distribution within the cell.…”
Section: Rna Targeting and Local Protein Translation In Dendritesmentioning
confidence: 99%
“…From each transcript, we obtained from RefSeq (rn4) the 3 ′ UTR sequence as well as the sequence of any cytoplasmically retained introns (Buckley et al 2011). To focus our search on smaller structure elements, we used a sliding window approach to split each 3 ′ UTR and intron sequence into several smaller segments.…”
Section: Application Of Nofold To Novel Motif Discoverymentioning
confidence: 99%
“…Previously, Buckley et al (2011) found that a ∼74-nt hairpin structure within the retained introns of several dendritic transcripts was sufficient to confer dendritic localization in rat hippocampal neurons. These structures were instances of the ID element, a type of rodent SINE retrotransposon element that likely arose from the dendritically localized BC1 gene (Kim et al 1994).…”
Section: Application Of Nofold To Novel Motif Discoverymentioning
confidence: 99%
“…By cutting branches, or dendrites, off neurons, Eberwine and his colleagues have discovered that RNA in dendrites can retain nucleotide sequences that target the RNA to that location 4 . They could not have found such information by analysing the RNA of an entire neuron.…”
Section: Profiling Heterogeneitymentioning
confidence: 99%